Geochemistry of CO2-Rich Gases Venting From Submarine Volcanism: The Case of Kolumbo (Hellenic Volcanic Arc, Greece) - Rizzo, Andrea Luca; Caracausi, Antonio; Chavagnac, Valérie; Nomikou, Paraskevi; Polymenakou, Paraskevi N.; Mandalakis, Manolis; Kotoulas, Georgios; Magoulas, Antonios; Castillo, Alain; Lampridou, Danai; Marusczak, Nicolas; Sonke, Jeroen E. (Frontiers in Earth Science, 2019)
Studies of submarine hydrothermal systems in Mediterranean Sea are limited to the southern Italian volcanism, while are totally missing in the Aegean. Here we report on the geochemistry of high-temperature fluids (up to 220°C) venting at 500 m b.s.l. from the floor of Kolumbo submarine volcano (Hellenic Volcanic Arc, Greece), which is located 7 km northeast of Santorini Island. Despite the recent unrest at Santorini, Kolumbo submarine volcano is considered more active due to a higher seismicity. Rizzo et al. (2016) investigated the He-isotope composition of gases collected from seven chimneys and showed that are dominated by CO2 (>97%), with only a small air contamination. Here we provide more-complete chemical data and isotopic compositions of CO2 and CH4, and Hg(0) concentration. We show that the gases emitted from different vents are fractionated by the partial dissolution of CO2 in water. Fractionation is also evident in the C-isotope composition (13CCO2), which varies between –0.04‰ and 1.15‰. We modelled this process to reconstruct the chemistry and 13CCO2 of intact magmatic gases before fractionation. We argue that the CO2 prior to CO2 dissolution in water had 13C ~ –0.4‰ and CO2/3He ~ 1•1010. This model reveals that the gases emitted from Kolumbo originate from a homogeneous mantle contaminated with CO2, probably due to decarbonation of subducting limestone, which is similar to other Mediterranean arc volcanoes (e.g. Stromboli, Italy). The isotopic signature of CH4 (13C ~ –18‰ and D ~ –117‰) is within a range of values typically observed for hydrothermal gases (e.g. Panarea and Campi Flegrei, Italy), which is suggestive of mixing between thermogenic and abiotic CH4. We report that the concentrations of Hg(0) in Kolumbo fluids are particularly high (~61 to 1300 ng m–3) when compared to land-based fumaroles located on Santorini and worldwide aerial volcanic emissions. This finding may represent further evidence for the high level of magmatic activity at Kolumbo. Based on the geo-indicators of temperature and pressure, we calculate that the magmatic gases equilibrate within the Kolumbo hydrothermal system at about 270°C and at a depth of ~1 km b.s.l..